Identification of suitable genotypes of lentil (Lens culinaris) for improved adaptation to rice fallow areas of Gangetic Alluvial Zone - Chatterjee, Shayree; Das, Arpita; Bhattacharya, Sudip; Banerjee, Joydeep; Gupta, Sanjeev; Agrawal, Shiv Kumar (Indian Council of Agricultural Research, 2023)
Rice fallows (RF) are the low lying kharif sown rice (Oryza sativa L.) areas that remain uncropped due to dearth of suitable cultivars of winter (rabi) pulses. A panel of 30 promising high yielding lentil (Lens culinaris Medik.) genotypes of diverse origin were assessed at both no till RF and with till condition at the Regional Research Substation (RRSS), Chakdah under the aegis of Bidhan Chandra Krishi Viswavidyalaya, Nadia, West Bengal for two years (2019–20 and 2020–21). Multi-trait performance (earliness, biomass and grain yield) of each genotype was considered during recommendation of suitable genotype for specific ecology deploying GGE biplot. The present study recommended IC 560183 for no till RF ecology and Moitree, IC 559996, ILL 7978 and L 1112-19 for with till ecology having specific adaptation. Additionally, 2011S-56212-2 and ILL 8006 were identified as ideal and desirable genotypes for both the ecologies and therefore, recommended for commercial cultivation across the areas of Gangetic alluvial zone for augmenting lentil production and productivity.